Analysis of Financial Statement Fraud Detection with Beneish M-Score at PT. Wilmar Cahaya Indonesia Tbk. - Panjaitan, Gloria; Athaya , Nada; Tamba, Rani; Safitri , Tsamara; Azzahra , An Suci (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2025)
Financial statements are a vital element in decision making by stakeholders such as investors, creditors, and regulators. However, it is not uncommon to find manipulation practices in the presentation of financial statements in order to display company performance that is better than reality. This study aims to analyze the potential fraud in the financial statements of PT Wilmar Cahaya Indonesia Tbk during the period 2020-2024 using the Beneish M-Score model. This model uses eight financial ratios to detect indications of accounting manipulation. The research method used is descriptive quantitative with secondary data obtained from the company's financial statements. The calculation results show that all Beneish M-Score values from 2020 to 2024 are above the -2.22 threshold, which indicates the potential for financial statement manipulation throughout the period. These findings indicate the need for more attention to the integrity of financial statements and the importance of implementing a stricter supervisory system.